Exploitation of aquatic resources for adornment and tool processing at Măgura 'Buduiasca' ('Boldul lui Moş Ivănuş') Neolithic settlement (southern Romania). (5th April 2018) - Mărgărit, Monica; Mirea, Pavel; Radu, Valentin
Abstract: Măgura 'Buduiasca' ('Boldul lui Moş Ivănuş') settlement has an important place among the Prehistoric settlements from the Balkans. It is characterized by continuous habitation from the Early Neolithic through to the Early Chalcolithic allowing an understanding of the development of utilitarian objects and personal adornments in respect of the raw materials used and their processing patterns. One group consists of local bivalves ( Unio sp.) which were exploited in an opportunistic manner: first as an important source of food and second as a source material for producing artefacts after recovery from domestic waste. The local gastropods shells ( Lithoglyphus sp., Theodoxus danubialis, Esperiana sp., Ansius/Planorbis sp.) are without any nutritional value and used only as a source of raw materials. They could be collected during specialized expeditions organized for this purpose at certain times of the year. Imported elements are a third category which most likely arrived at Măgura 'Buduiasca' as finished objects. They provide evidence for complex exchange networks at this period in prehistory. Species like Mytilus or Cardium most likely come from the Black Sea, while Spondylus or Glycymeris may have their origins in the Mediterranean Sea. The presence of these raw materials demonstrates different transformation methods with their origin influencing the processing procedure: allogene valves for adornments, while Unio sp. are especially transformed into utilitarian tools.